Phenotypes of Non-Alcoholic Fatty Liver Disease in Different Regions of the Russian Federation, Diagnostic and Therapeutic Approach in Clinical Practice - V. T. Ivashkin; M. S. Zharkova; N. V. Korochanskaya; I. B. Khlynov; Yu. P. Uspensky (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim: to present data on the prevalence of various phenotypes of non-alcoholic fatty liver disease (NAFLD), the features of its diagnosis and treatment in various regions of the Russian Federation following a meeting of chief gastroenterologists.Key points. Non-alcoholic fatty liver disease (NAFLD) holds the leading position among non-infectious liver diseases in the Russian Federation, its prevalence is 37.3 % and does not tend to decrease.To get information on various aspects of NAFLD diagnosis and treatment, opinion of 18 chief external regional gastroenterologists and leading specialists in the field of liver diseases was studied by analyzing the responses to questions specially formulated for them. Information on the situation in the Ural, Privolzhsky, Southern, Central and North-western Federal Districts was obtained. Regional statistics on the prevalence of NAFLD and its certain phenotypes (steatosis, steatohepatitis, cirrhosis), diagnostic instruments and treatment approaches which are used in clinical practice, as well as on the most common associated conditions was presented.Conclusions. The collected information allows to improve both administrative and treatment and diagnostic-related activities in managing patients suffering from this disease.